Oral Lichen Planus: Manifestation of Grinspan’s Syndrome or a Lichenoid Reaction to Medications - Zain Akram, Malik Adeel Anwar, Sahar Iqrar, Maria Noor, Salima Naveed Manji, Hajira Arham (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction/Objectives: Oral lichen planus is a condition of chronic nature and has no defined etiology. Oral lichen planus has been linked to several disorders such as hepatitis, hypertension, hypothyroidism, and hypercholesterolemia. The objective was to determine the link between the mucosal variant of lichen planus and systemic diseases, namely hypertension and diabetes mellitus. This triad is named Grinspan’s Syndrome. No previous studies have confirmed a true relation between the three diseases. Material and methods: Almost 1100 patients presented to the dental diagnostics department, out of which 89 were diagnosed with oral lichen planus clinically. Both males and females were included in the study. Age was variable in all these patients. A detailed history proforma was used to record their history and clinical diagnosis. Results: From the pool of patients that had lichen planus (n=89), almost half, 41.6% (n=37) had hypertension. Not all these patients had been prescribed, nor had been taking anti-hypertensives for their condition. 59.5% (n=22) of these 89 individuals were taking medicines for their hypertensive state. 24.7% (n=22) individuals had diabetes mellitus but not all were on oral or injectable hypoglycemics. Infact, 72.7% (n=16) out of these 22 diabetics had been taking medicines for hyperglycemia. Conclusion: On account of obtained medical history, majority of the patients with either hypertension or diabetes had been taking medicines for their systemic condition. The list of drugs included oral hypoglycemics, beta-blockers, diuretics, and calcium-channel blockers. All these drugs are notorious for giving rise to the condition called lichenoid reactions. For determination of accurate results, it is necessary at both histopathological and molecular level to rule out the possibility of lichen planus before labelling the condition as lichenoid reactions caused by drugs. This can help in declaring such patients as truly having Grinspan’s Syndrome. Keywords: Grinspan’s syndrome, hypertension, diabetes mellitus, oral lichen planus